Peace jobs: A student’s guide to starting a career working for peace (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Peace jobs: a student’s guide to starting a career working for peace by David J. Smith, a volume in the series: Peace Education, editors Laura Finley & Robin Cooper, Information Age Publishing, 2016, 183 pp., US $45.99 (paperback), US $85.99 (hardcover), ISBN 978-1-68123-330-7.